Optimizing the growth of pangas catfish seeds through the addition of spirulina in feed - Harmilia, Elva Dwi; Khotimah, Khusnul; Nofianti, Rini (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
Pangasius catfish (Pangasius sp.) was an important commodity in Indonesia. High demand in the market requires production to be carried out actively. Adding spirulina as a supplement to feed was a way to increase the growth of pangasius catfish seeds for optimal production. The aimed of the research was to determine the effect of spirulina on the growth of pangasius catfish seeds which were added to pelleted feed. The research used a completely randomized design with four levels of treatment. Treatment 1 (100g commercial pellets + 3g spirulina), treatment 2 (100g commercial pellets + 5g spirulina), treatment 3 (100g commercial pellets + 7 g spirulina), treatment 4 (100g commercial pellets + 9g spirulina). The parameters observed were growth of length, weight, survival, and water quality (pH, temperature and dissolved oxygen). The study results showed that the addition of 7 g spirulina had the best effect on growth with a length of 5.25 cm and a weight of 6.74 g. Meanwhile, the lowest occurred when adding 9 g of spirulina with a length of 4.08 cm and a weight of 5.78 g. There was no mortality during maintenance so that the survival rate of pangasius catfish seeds was 100% in each treatment. So the addition of spirulina to feed has an effect on the growth of pangasius catfish. However, if ftoo much spirulina was added, the effect will not be optimal.